(12,5-Х): 5 = (3,6 + Х): 6

(12,5-Х): 5 = (3,6 + Х): 6

  • (12,5-x) * 6 = 5 (3.6 + x)
    (-x + 25/2) * 6 = 5 (x + 18/5)
    -2x + 25/2 * 6 = 5 * 5x + 18/5
    (-2x + 25) * 6/2 = 5 (5x + 18) / 5
    (-2x + 25) * 6 * 5 = 2 * 5 (5x + 18)
    (-2x + 25) * 30 = 10 (5x + 18)
    -30 * 2x + 750 = 10 * 5x + 180
    -60x + 750 = 50x + 180
    -60x = 50x-570
    -110x = -570
    x = -57 / -11
    x = 57/11
  • зліва і з права помножити на 30 (6 * 5) отримаємо

    6 (12,5-х) = 5 (3,6 + х)

    75 - 6х = 18 + 5х

    11х = 57

    х = 57/11

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *

7 + 1 =